Homogenisation of water and sediment bacterial communities in a shallow lake (lake Balihe, China). (14th November 2022) - Zhong, Meifang; Capo, Eric; Zhang, Huayong; Hu, Haiyan; Wang, Zhongyu; Tian, Wang; Huang, Tousheng; Bertilsson, Stefan
Abstract: Planktonic and benthic bacterial communities hold central roles in the functioning of freshwater ecosystems and mediate key ecosystem services such as primary production and nutrient remineralisation. Although it is clear that such communities vary in composition both within and between lakes, the environmental factors and processes shaping the diversity and composition of freshwater bacteria are still not fully understood. In order to assess seasonal and spatial variability in lake bacterial communities and identify environmental factors underpinning biogeographical patterns, we performed a large‐scale sampling campaign with paired water and sediment sample collection at 18 locations during four seasons in Lake Balihe, a subtropical shallow fish‐farming lake in mid‐eastern China. Pelagic and benthic bacterial communities were distinctly different in terms of diversity, taxonomic composition and community structure, with Actinobacteria, Bacteroidetes, Cyanobacteria and Alphaproteobacteria dominating lake water, and Acidobacteria, Bacteroidetes, Chloroflexi, Gammaproteobacteria and Deltaproteobacteria dominating sediment. Nevertheless, these two communities had stronger spatial concordance and overlap in taxa during spring and autumn seasons. Together, the main drivers of both the spatial and temporal variations in Lake Balihe bacterial communities were identified as water temperature, turbidity, nitrogen and phosphorus availability, and thermal stratification controlled by wind‐mixing and activity of the dense farmed fish populations. Notably, populations affiliated with Firmicutes, known to be abundant in fish gut microbiome, were especially abundant in the summer season and locations where high fish biomass was found, suggesting a potential link between fish gut microbiome and the pelagic bacterial communities. Our findings demonstrated seasonal homogenisation of pelagic and benthic bacterial communities linked to marked shifts in a set of seasonally‐driven environmental variables including water temperature and nutrient availability.